Incorporating Technology among Young Learners: The use of the Interactive Whiteboard in the English Classroom - Martin, Daniela Roza (Revista da Graduação, 2011)
Digital technologies have created a new way of learning and communicating in the world. Notwithstanding, even being overwhelmed by technology, having the digital advances integrated into the school curriculum is still a desire for many students. It is acknowledged that in the city of Porto Alegre (RS) some institutions have already purchased the Interactive Whiteboard (IWB), known as the most up-to-date resource available for educators today. However, even having a good tool to promote more interactive classes, there are teachers who still resist using it, and as a result, do not take advantage of all benefits this resource offers. Taking these facts into consideration, this paper aims at making a reflection on how important it is to incorporate ICT in English classes for young learners. Moreover, it aims at presenting a project proposal in order to encourage EFL teachers to take the first step toward IWB implementation in their classes. This paper also presents a list of useful IWB websites in order to help teachers who are still not familiar with this tool. Finally, it is possible to claim that it is not the technology that decides how effectively the IWB will be used in their classroom. Good-quality teaching by committed educators is the answer to more effective learning with the IWB.